Optimal parameter in theeconomic pipeline distribution of jatropha oil (2011)
Due to gradual depletion of world petroleum reserves and the environmental pollution of increasing exhaust emissions, there is an urgent need to develop alternative energy resources, such as biodiesel fuel. One way of reducing the biodiesel production costs is to use the less expensive feedstock containing fatty acids such as inedible oils, animal fats, waste food oil and by products of the refining vegetables oils. The fact that Jatropha oil cannot be used for nutritional purposes without detoxification makes its use as energy or fuel source very attractive as biodiesel. Due to its high flash point, Jatropha oil has certain advantages like greater safety during storage, handling, and transport. However, this may create problems during starting. The viscosity of Jatropha oil is less as compared with other vegetable oils but it is higher than diesel. To lower the viscosity and density of Jatropha oil, preheating is necessary prior to pumping. However, additional costs are incurred through heating and heating cost increases with temperature. This suggests the existence of an optimum temperature to which the fluid can be heated at minimum cost. This work is therefore, a study carried out to determine the optimum heating temperature for a given pipe diameter. The study of fluid flow was carried out and modified to incorporate cost concept to produce a mathematical model that predicts the economic heating temperature. The effect of pipe diameter on these temperatures was investigated via a computer code developed in Matlab 7.3 programming language. The result obtained showed that as the pipe diameter increased from 0.042m to 0.062m, the optimum heating temperature is maintained at 30°C. Results of this nature can be utilized in industries where pumping of Jatropha oil as an alternative fuel is sine-qua-non.